Kulturschock in Brasilien - Eine Studie zur Interkulturalität in Ina von Binzers Briefroman Leid und Freud einer Erzieherin in Brasilien (1887) - Schamm, Christoph (Contingentia, 2008)
In the years around 1880 the concepts of modern culture studies were still largely unknown. The term ’cross-culture experience’ that is now part of the standard vocabulary of today’s human sciences had not yet been invented. And yet the heyday of colonialism saw the publication of numerous texts that analysed the experience of the strange and unfamiliar with remarkable sensitivity. The German governess Ina von Binzer was twenty-four when she left for a two-year visit to Brazil, where she worked with the family of a wealthy coffee plantation owner. On her return to Germany she turned her diary jottings into a fictionalised epistolary novel, describing in great detail the domestic and social reality of the Segundo Império, while also depicting the way in which the daily experience of otherness gradually increased in intensity until it became a very real feeling of culture shock. On the strength of its conscious struggle with the sense of being different and alien, Binzer’s work may be characterised as a ’culture study avant la lettre’.